Basic Principle of sincere cooperation in European Union Law - Dragišić, Radmila (Glasnik Advokatske komore Vojvodine, 2022)
Although its legal nature is somewhat broader, compared to other basic principles governing the relationship between European Union law and the internal law of member states, the principle of loyal or "sincere" cooperation under the Lisbon clarifications is one of the central content and development building elements on which the legal order of the European organization is grounded. Therefore, we focus on the concept and content of this principle, its origin and genesis, as well as the scope of its application in relation to directives as formal sources of EU law, whereas the views of the Court of Justice contribute the most to the overall analysis. We use analytical and synthetic methods in our research, with content analysis and historical-comparative analysis occupying a central place within them. At the end, we bring key considerations, the most indelible of which are that the principle of sincere cooperation belongs to the tools through which national differences can be reduced in order to achieve the goals of the European organization, and that the assumption for that, among other things, is to eliminate malformations between this principle and the directive as a secondary source of European Union law.
Keywords: EU Law, internal law of member states, basic legal principles, basic legal principle of sincere cooperation, case law of the EU Court of Justice